From classic to contemporary: is marketing updating or upgrading? - Wang, Titi (2006)
This paper reviewed the current popular debates on the changing nature of marketing theory and practice. The author intends to do a research on this change mainly caused by new technology and information, in order to find if this change is revolutionary or evolutionary to marketing theory and practice. By employing the case study research method, this paper having a look at the new online marketing strategy of Nike Inc. is going to realease the nature of the changing marketing.